THE EFFECT OF AMYLUM ADHESIVE AND SAWDUST COMPOSITION FOR RUBBER SEED SHELL BIO-BRIQUETTE AS AN ENVIRONMENTALLY FRIENDLY ALTERNATIVE FUEL - Pratiwi, Fathia Eka; yenica, Pitri; Putri, Maulidia (Jurnal Indonesia Emas PPI Dunia, 2018)
and amylum adhesive. Experiments were carried out in several stages: aggregate of the raw materials, drain the raw materials, do carbonization or combustion with 600â temperature for 2 hours, restrict the supply of oxygen so that the materials do not burn to ashes, sieve the materials, weigh each of ingredients in the ratio of 60:20:20, 50:20:30, 40:20:40, and 30:20:50, blend the materials, print the briquettes, drain, and analyze the contents of briquette. This reasearch generates optimum compositionwith ratioof 60% rubber seed shells, 20% sawdust and 2 % amylum adhesive. It is in terms of the parameters that have been analyzed in the form of spesification of inherent moisture is 4.99%, ash content is 4.38%, volatile matter content is 24.75%, fixed carbon is 66.38% and calorific value is 6069 cal/gr.